2017
DOI: 10.1007/s10695-017-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

One evidence of cocaine- and amphetamine-regulated transcript (CART) has the bidirectional effects on appetite in Siberian sturgeon (Acipenser baerii)

Abstract: Cocaine- and amphetamine-regulated transcript (CART), discovered in 1995, with various biological functions, has received much attention recently due to its role in the regulation of appetite in mammals. However, the function of CART on the appetite control in fish species is still not very clear. In this study, Siberian sturgeon (Acipenser baerii Brandt) cart gene was cloned for the first time, and the cart mRNA levels in 11 feeding-related tissues was investigated. The Siberian sturgeon cart gene sequence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
3
13
1
Order By: Relevance
“…Hence, in Atlantic salmon, hypothalamic cart2b might play a vital role in appetite regulation, with fasting maybe inducing shutting down hunger. This is in line with observations in Siberian sturgeon (Acipenser baerii) (Zhang et al, 2018), where cart mRNA in whole brain increased after 3-17 days of food deprivation. Interestingly, our finding is contrary to several previous studies that demonstrate the anorectic function of Cart.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, in Atlantic salmon, hypothalamic cart2b might play a vital role in appetite regulation, with fasting maybe inducing shutting down hunger. This is in line with observations in Siberian sturgeon (Acipenser baerii) (Zhang et al, 2018), where cart mRNA in whole brain increased after 3-17 days of food deprivation. Interestingly, our finding is contrary to several previous studies that demonstrate the anorectic function of Cart.…”
Section: Discussionsupporting
confidence: 92%
“…In general terms, appetite-stimulating or orexigenic factors, including NPY (85, 86), and orexin (89, 90), have been shown to display periprandial changes characterized by higher expression levels before or at mealtime, and lower levels post feeding, suggesting that they are hunger signals. By contrast, appetite inhibiting or anorexigenic signals, such as CART (91, 92), were found to be mainly upregulated after a meal, thus acting as a postprandial satiety signal.…”
Section: Nutritional Regulation Of Hormones Modulating Food Intake Inmentioning
confidence: 88%
“…In this respect, several central and peripheral appetite regulators are affected by a single meal, showing periprandial fluctuations in their expression and/or secretion levels. Brain hormones showing such changes in fish include NPY (85, 86), orexin (8790), CART (87, 88, 91, 92), and nesfatin-1 (93). In general terms, appetite-stimulating or orexigenic factors, including NPY (85, 86), and orexin (89, 90), have been shown to display periprandial changes characterized by higher expression levels before or at mealtime, and lower levels post feeding, suggesting that they are hunger signals.…”
Section: Nutritional Regulation Of Hormones Modulating Food Intake Inmentioning
confidence: 99%
“…Numerous vital and outlying appetite regulators are affected by a lone meal, displaying prior feeding vacillations in their expression and/or secretion levels. Brain hormones demonstrating such changes in teleost include Npy [9,81], which is of interest in this review; orexin [45,82,87,88]; cocaine-and amphetamine-regulated transcript (CART) [18,[87][88][89]; and nesfatin-1 [90].…”
Section: Neuropeptide Y-its Role As Feed Regulator In Teleostmentioning
confidence: 99%
“…Knowledge about neuroendocrine control on food intake and regulation, including neuropeptide Y (Npy) and peptide YY (Pyy), explicitly concerning their roles, has significantly improved nowadays. Current studies have indicated that these peptides have impacts on the feeding behavior in vertebrates (teleost) [12,14,[16][17][18] either as an orexigenic or anorexigenic factor.…”
Section: Introductionmentioning
confidence: 99%